Hematologic and oncologic complications in the critically ill child. - McIntosh, S. (Yale Journal of Biology and Medicine, 1984)
Admission of a patient to an intensive care unit for management of direct consequences of a hematologic or oncologic disease is occasionally necessary. Such problems included exchange transfusion, sepsis, compression of vital structures by malignant tumor, metabolic derangements, leukostasis, post-operative care, major sickling episodes in vital organs, and disseminated coagulopathy. More often, however, hematologic complications arise in the child critically ill from other causes, such as trauma or infections. The first two sections of this review address blood transfusion and hemostasis, topics likely to have wide application in the care of critically ill children. The last portion discusses problems unique to patients with sickling or malignant disease.